2017
DOI: 10.1007/s00280-016-3237-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b study of pembrolizumab (MK-3475; anti-PD-1 monoclonal antibody) in Japanese patients with advanced melanoma (KEYNOTE-041)

Abstract: PurposeThis phase I b study evaluated the safety and anti-tumor activity of pembrolizumab in Japanese patients with advanced melanoma.MethodsPembrolizumab (2 mg/kg) was given every 3 weeks (Q3W) for up to 2 years or until confirmed progression or unacceptable toxicity. The tumor response was assessed as per the Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1) by both investigator review and central review.ResultsForty-two patients with advanced melanoma received pembrolizumab. A primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 30 publications
7
85
0
Order By: Relevance
“…The safety profile of pembrolizumab in this study was generally similar to that reported in previous studies evaluating pembrolizumab monotherapy in patients with advanced NSCLC . The finding that pembrolizumab was well tolerated in Japanese patients is consistent with results from the KEYNOTE‐041 study, which found pembrolizumab to be well tolerated in Japanese patients with advanced melanoma . The most common treatment‐related AE in our study were malaise, diarrhea and rash.…”
Section: Discussionsupporting
confidence: 89%
“…The safety profile of pembrolizumab in this study was generally similar to that reported in previous studies evaluating pembrolizumab monotherapy in patients with advanced NSCLC . The finding that pembrolizumab was well tolerated in Japanese patients is consistent with results from the KEYNOTE‐041 study, which found pembrolizumab to be well tolerated in Japanese patients with advanced melanoma . The most common treatment‐related AE in our study were malaise, diarrhea and rash.…”
Section: Discussionsupporting
confidence: 89%
“…However, the efficacy of nivolumab monotherapy in MM was not known because of its rarity. In Japanese clinical trials of anti‐PD‐1 monotherapy for advanced melanoma, the ORR for nivolumab and pembrolizumab was 34.8% and 24.3%, respectively, whereas the DCR for nivolumab and pembrolizumab was 65.2% and 48.6%, respectively. In comparison, the ORR and DCR in MM were 30% and 56%, respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Because the Japanese melanoma population possesses a high ratio of acral lentiginous melanoma and mucosal melanoma 9 with low levels of TMB, 8 the efficacy of anti-PD-1 Ab in the Japanese population is lower than that in Caucasian populations. [1][2][3] For the patients with anti-PD-1 Ab-failed advanced melanoma, ipilimumab is another choice, especially for melanoma without the BRAF gene mutation. 10 However, because the efficacy of ipilimumab in patients with nivolumab-resistant melanoma is extremely low after objective tumor progression, 5 radiotherapy is sometimes administrated in combination with ipilimumab.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anti‐programmed death 1 (PD‐1) antibody (Ab) monotherapy has been one of the first‐line therapies for the treatment of advanced melanoma, especially for BRAF mutation‐negative melanoma . However, its efficacy rate is 24.1–34.8% in the Japanese population, which is lower than that of a previous clinical trial in another country (43.7%) .…”
Section: Introductionmentioning
confidence: 99%